Development of Contextual Based Augmented Reality Science Learning Media to Improve Critical Thinking Skills of Junior High School Students - Aliyanti, Cindi; Wicaksono*, Iwan; Doru, Mustafa; elik, Melahat; Ridlo, Zainur Rasyid (Jurnal Pendidikan Sains Indonesia, 2025)
The critical thinking skills (CTS) of junior high school students remain relatively low, partly due to the limited use of interactive and contextual learning media. This study aims to develop augmented reality (AR)-based science learning media using a contextual approach to enhance students CTS. The media was developed using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. Media validity was assessed by three expert validators, while practicality and effectiveness were tested through observation, questionnaires, and pretest-posttest on grade VII H students at Junior High School 7 Jember. The results showed that the AR-based media had excellent validity (88%) and very high practicality (96.52%), indicating ease of use in learning. Its effectiveness in improving CTS was shown by an average N-Gain score of 0.77 (high category). Students responses were also very positive, with an average of 81.6%. This AR media features interactive 3D visuals linked to real-life contexts, making science concepts like motion and force easier to understand and helping to foster CTS. Technical challenges, such as internet dependence, can be addressed by using projection tools in the classroom. In conclusion, contextual-based AR media is valid, practical, and effective for supporting 21st-century science learning